Lantibiotics: A Candidate for Future Generation of Antibiotics (Stamford Journal of Microbiology, 2011)
Emergence of multi-resistant pathogens has urged the exploration of antibiotic repertoires. The long reliability on the glycopeptide antibiotic vancomycin against fatal diseases caused by Gram-positive bacteria is also in wrecked to insist on finding more promising alternative antibiotics. The peptide antibiotic nisin is effective against vancomycin resistant bacteria. Nisin is the first lantibiotic that was discovered before penicillin and has been widely used as a safe alternative for chemical reagents in food preservation in around 50 countries for over 40 years without natural resistance development. Therefore, lantibiotics are one of the most promising alternative candidate for future antibiotics that maintain their antibacterial efficacy by many modes of action. Till now, more than 60 lantibiotics have been isolated, identified and characterized. We explained various aspects of biosynthesis, grouping, mutagenesis, activities and modes of action of lantibiotics in this review. DOI: http://dx.doi.org/10.3329/sjm.v1i1.9096 Stamford Journal of Microbiology, Vol.1(1), July 2011, p.1-12